Kepemimpinan Tranformasional Kepala Sekolah dalam Meningkatkan Kinerja Guru - Yuliastuti, Lisa Aprelia; Felita, Almira Vashti; Nawangsari, Dewi Cantika; Wulandari, Rahma Ayu; Ningrum, Refkli Lifdia Kusuma; Wulandari, Ayu; Nuphanudin, Nuphanudin (Lembaga Yasin AlSys, 2024)
The principal is the leader of the educational unit. The leadership success of a school principal is based on one of several leadership theories or models. One leadership model is transformational leadership. Transformational leadership is leadership that has the ability to change the energy of resources, be they people, tools, or situations, to achieve goals. Transformational leadership has the following characteristics: charismatic, the ability to create inspiration, the ability to stimulate the minds of followers positively, individual attention. Transformational leadership has the following characteristics: having a vision, having personal considerations, inspirational motivation, intellectual simulation. The application of the principal's transformational leadership style is seen in: the ability to build the school's vision, mission and programs, be an agent of change, be charismatic, have empathy, stimulate intelligence and encourage creativity, creating opportunities for all school members. The application of transformational leadership carried out by school principals has an impact on the achievement of professional learning. Creating a school culture and environment that supports and achieves high student learning outcomes.